Arthroscopic Guided Synovial Biopsies - Orr, Carl Kieran (Front Med (Lausanne), 2021)
Synovial tissue can be safely and reliably collected for research and clinical purposes using arthroscopy. This technique offers the obvious advantage of allowing direct visualization, and targeted biopsy of specific areas of interest within the joint, as well as for the collection of tissue which will include a lining layer. Much has been learnt by studying the synovium retrieved using this technique concerning the pathobiology of inflammatory arthritis. Furthermore, recent evidence suggests that the tissue retrieved may enable the identification of unique pathotypes that will allow for a precise approach to treatment selection in individual patients. Although ultrasound guided techniques for sampling synovial tissue have gained in popularity over the last decade, both methodologies are expected to compliment each other, each having unique benefits and drawbacks. We present here a detailed description of the arthroscopy technique reporting on our collective experience at two centers in Europe.